A Case of Recurrent Schizencephaly with Prenatal and Postnatal Ultrasound and Magnetic Resonance Imaging Details - Eka, Sowjanya; Vikraman, Seneesh Kumar; Puthenveettil, Shanas Kangatt; Chandran, Pillai Divya; Urangat, Prashobh Raj; Chandran, Rijil; Murugan, Smitha (Journal of Fetal Medicine, 2025)
Schizencephaly is a rare congenital disorder of cerebral cortical development classified under cell migration defects. Here we report a case of recurrent schizencephaly diagnosed prenatally and confirmed postnatally in two consecutive pregnancies of a nonconsanguineous couple. Prenatal ultrasound is a valuable tool for the early detection, evaluation, and management of schizencephaly. Magnetic resonance imaging complements the diagnosis of schizencephaly by confirming the diagnosis and providing information on additional abnormalities such as polymicrogyria, heterotopias, and closed lip schizencephaly. Whole exome sequencing revealed a heterozygous missense variant in exon 1 of the PEX13 gene, associated with peroxisome biogenesis disorder type 11A (Zellweger syndrome). Our case highlights the potential genetic etiology of schizencephaly.
Keywords: schizencephaly; prenatal diagnosis; PEX13 gene; zellweger syndrome; nonconsanguineous marriage